GARLIC GROWING TECHNOLOGY - Eshdavlatov , Akmal; Pirnzarova , Madina (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article analyzes the morphological structure of garlic and the technologies for its cultivation. Garlic is a crop that is demanding in terms of fertilizers, resistant to cold, and highly productive. Garlic cloves used for planting must meet agrotechnical requirements: they should have high germination rates, be free from diseases, undamaged, and of sufficient weight.